Influence of the composition of zinc-ethyl silicate paints on electrochemical properties - Romagnoli, Roberto (1994)
The protection of steel by zinc-ethyl silicate primers is based on the general principle of cathodic protection by metallic zinc in contact with a ferrous substrate. The influence of the zinc content on the paint behaviour has been studied, but little attention has been paid to effects caused by the incorporation of additives, such as extender pigments, to the formulation. The aim of this paper is to study the influence of the whole composition of zinc-ethyl silicate paints on their electrochemical properties. A second purpose is to establish the nature of the anticorrosive action of these paints. Four commercial zinc-ethyl silicate paints were chosen for these investigations. It was found that the incorporation of extender pigments modified the behaviour of these paints. The anticorrosive action was due to the cathodic protection by zinc powder and the inhibition of the electrochemical reactions by corrosion products. The barrier effect, in the sense of ohmic resistance, provided by these paints was of lesser importance.